The impact of Covid-19 pandemic on obstetrics & gynaecology specialist training in Malaysia: perception of clinical postgraduate students - Yahaya, Ahmad Shuib; Abdul Hamid, Habibah; Abdul Ghani, Nur Azurah; Awang Besar, Mohd Nasri (Universiti Putra Malaysia, 2022)
Introduction: The COVID-19 pandemic that strucked the world had changed the global health system and caused changes in clinical practice and practitioners’ exposure. The aim of this research is to study the perception of UKM Obstetrics and gynaecology postgraduate students about the impact of COVID-19 pandemic on their specialist training. Methods: The survey had been carried out through Google Form among students enrolled in Doctor of Obstetrics & Gynaecology (DROG) program in UKM and consist of three sections; socio-demographic information, changes in role during COVID-19 and perception towards training. Quantitative analysis performed using Statistical Package for the Social Sciences (SPSS). Results: Out of 47 respondents, 13 were working in MOH hospitals, 17 in UKM Hospital and 17 in both MOH and UKM hospitals. Total of 32 students (68.1%) felt increment in seeing obstetric patients and 31 students (65.9%) performed more obstetric procedures during COVID-19 pandemic. For gynaecology, 29 students (61.7%) claimed had been seeing less gynaecological patients and 40 students (85.1%) performed less gynaecological surgeries. Total of 35 students (74.5%) agreed that COVID-19 pandemic had affected their mental well-being and 42 students (89.4%) agreed their social well-being had been affected. Total of 43 trainees (91.5%) agreed that COVID-19 pandemic had negatively impacted their surgical skills in gynaecology and 38 students (80.1%) claimed their overall learning opportunities had been affected. Mean for training perception score is 52.53 and there is no significant difference in score mean among students according to difference in study year and training hospitals. Conclusion: COVID-19 pandemic had caused negative impact to the specialty training among Obstetrics & Gynaecology postgraduate students in UKM.